Design and synthesis of nanoscaled IQCA-TAVV as a delivery system capable of antiplatelet activation, targeting arterial thrombus and releasing IQCA - Wu, Jianhui (Int J Nanomedicine, 2018)
BACKGROUND: Arterial thrombosis has been associated with a series of pathological conditions, and the discovery of arterial thrombosis inhibitor is of clinical importance. METHODS: By analyzing the pharmacophores of anti-platelet agents, thrombus targeting peptide and anti-thrombotic nano-systems 3S-1,2,3,4-tetrahydroisoquino-line-3-carbonyl-Thr-Ala-Arg-Gly-Asp(Val)-Val (IQCA-TAVV) was designed and prepared as a nano-scaled arterial thrombosis inhibitor. RESULTS: In vitro the nanoparticles of IQCA-TAVV were able to adhere onto the surface of activated platelets, attenuate activated platelets to extend pseudopodia and inhibit activated platelets to form aggregators. In vivo IQCA-TAVV targeted arterial thrombus, dose dependently inhibited arterial thrombosis with a 1 nmol/kg of minimal effective dose, and the activity waŝ1670 folds of that of aspirin. CONCLUSION: IQCA-TAVV represented the design, preparation and application of nanomedicine capable of adhering on the surface of activated platelets, attenuating platelet activation, targeting arterial thrombus and inhibiting arterial thrombosis.